Section 16(b): Insider Trading (Washington University Law Quarterly, 1974)
This Article analyzes the elements of Section 16(b) of the 1934 Securities Exchange Act, as well as the common law history of insider trading.
Keywords: Insider trading; Speculation; Fiduciary duties